Highly informative integrated method for determining the type of engine oil - A. Mamykin; O. Kukla; L. Matvienko; G. Dorozinska; V. Maslov; G. Dorozinsky (Tekhnologiya i Konstruirovanie v Elektronnoi Apparature)
The presence of correlation dependences between the type of motor oil and its refractometric and electrophysical characteristics (refractive index, specific resistance and dielectric constant) is experimentally shown. Methods for determining the type of engine oil are proposed, based on the measurement of these characteristics, as well as prototypes of portable measuring devices that implement these methods. Impedance spectroscopy was used to determine the resistivity and dielectric constant, and a device based on the effect of surface plasmon resonance was used to determine the refractive index. It is shown that the accuracy of identification of the type of motor oil increases significantly with simultaneous consideration of all above physical characteristics. It is shown that this complex method can most accurately detect, on the one hand, purely synthetic motor oils, on the other hand, oils with a mineral component (semi-synthetic and mineral). The results of the studies can be used to identify the type of motor oil as well as to detect forgery.